Editorial: Special issue of the 5th Symposium of the European Association of Research in Transportation - Cranenburgh, Sander van; Dekker, Thijs (European Journal of Transport and Infrastructure Research, 2018)
This special issue presents seven selected papers from the 5th Symposium of the European Association of Research in Transportation (hEART) which was held in September 2016 in Delft, The Netherlands, and was organised by Delft University of Technology. The contributions cover a wide range of topics in transportation, reflecting the broad scope of the hEART symposium series, including but not limited to travel behaviour, travel survey methods, railway freight as well as (terminal) logistics. As editors of this special issue we are very grateful for the efforts made by the authors, in particular their enduring efforts to push the quality of their contributions to a higher level during the review process. Also, we like to take the opportunity to thank all the reviewers for their constructive feedback and suggestions for improvement. This editorial provides a brief overview of the hEART2016 symposium. After that, an overview is given of the seven contributions that form this special issue.